Training on Movement Figure-Ground Discrimination Remediates Low-Level Visual Timing Deficits in the Dorsal Stream, Improving High-Level Cognitive Functioning, Including Attention, Reading Fluency, and Working Memory - Lawton, Teri; Shelley-Tremblay, John (Frontiers in Human Neuroscience, 2017)
The purpose of this study is to determine whether neurotraining to discriminate a moving test pattern relative to a stationary background, figure-ground discrimination, improves vision and cognitive functioning in dyslexics, as well as typically-developing normal students. We predict that improving the speed and sensitivity of figure-ground movement discrimination (PATH to Reading neurotraining) remediating visual timing deficits in the dorsal stream, improves processing speed and reading fluency, and the executive control functions of attention and working memory in both dyslexic and normal students who had PATH neurotraining more than in those students who had no neurotraining. This prediction was evaluated by measuring whether dyslexic and normal students improved on standardized tests of cognitive skills following neurotraining exercises, more than following computer-based guided reading (Raz-Kids). The neurotraining used in this study, visually-based training designed to improve magnocellular function at both low and high levels in the dorsal stream, the input to the executive control networks coding working memory and attention, represents a paradigm shift from the phonologically-based treatment for dyslexia, which concentrates on high-level speech and reading areas. This randomized controlled-validation study was conducted by training the entire 2nd and 3rd grade classrooms (42 students) for 30 minutes twice a week before guided reading. Standardized tests were administered at the beginning and end of 12-weeks of intervention training to evaluate improvements in academic skills. Only movement-discrimination training remediated both low-level visual timing deficits and high-level cognitive functioning, including selective and sustained attention, reading fluency, and working memory for both dyslexic and normal students. Remediating visual timing deficits in the dorsal stream revealed the causal role of visual movement discrimination training in improving high-level cognitive functions such as attention, reading acquisition, and working memory. This study supports the hypothesis that faulty timing in synchronizing the activity of magnocellular with parvocellular visual pathways in the dorsal stream is a fundamental cause of dyslexia and being at-risk for reading problems in normal students, and argues against the assumption that reading deficiencies in dyslexia are caused by phonological or language deficits, requiring a paradigm shift from phonologically-based treatment of dyslexia to a visually-based treatment.